Asset Forfeiture of Corruption Proceeds Using the Non-Conviction Based Asset Forfeiture Method: A Review of Human Rights - Wulandari; Wasis Suprayitno; Kukuh Dwi Kurniawan; Merve Özkan Borsa (Indonesia Law Reform Journal, 2023)
Abstract One of the state's efforts to eradicate corruption is to draw up a Bill on Asset Write-off, in which there is the regulation regarding the concept of Non-Criminal-Based Asset Write-off, which this concept can be called "Writing Without Punishment". The purpose of this writing is to find out how the concept of Non-Conviction Based Asset Forfeiture "Forfeiture Without Criminalization" can overcome corruption cases. Then to know how the human rights of the perpetrators whose assets are seized all by the state, doesn't every human being have the right to defend what they are entitled to. The method used by the author is the normative juridical method. These things are the general description of In this study, it was concluded that "Non-Conviction Based Assets" Forfeiture (NCB)" in the case of confiscation of assets resulting from criminal acts of corruption intends to maximize efforts to restore / recover assets (asset recovery) for state treasury losses are for the benefit of justice with the whole community, and the mechanism does not violate Human rights are based on the barrier between the rights to property as defined regulated in "Article 28G of the 1945 Constitution of the Republic of Indonesia. Keywords: Non-Conviction Based Asset Forfeiture; Corruption; Criminal Code. Abstrak Salah satu upaya negara memberantas korupsi adalah dengan lahirnya Rancangan Undang-undang Penghapusan Aset, yang didalamnya terdapat pengaturan mengenai konsep Penghapusan Aset Berbasis Non-Pidana yang konsep ini dapat disebut dengan "Penghapusan Tanpa Hukuman". Tujuan dari penulisan ini adalah untuk mengetahui bagaimana konsep Penghapusan Aset Berbasis Non-Pidana "Penghapusan Tanpa Kriminalisasi" dapat mengatasi kasus korupsi. Kemudian untuk mengetahui bagaimana hak asasi manusia dari pelaku yang asetnya disita seluruhnya oleh negara, bukankah setiap manusia berhak membela apa yang menjadi haknya. Metode yang digunakan oleh penulis adalah metode yuridis normatif. Hal-hal tersebut merupakan deskripsi umum dalam penelitian ini, dinyatakan bahwa "Penghapusan Aset Berbasis Non-Pidana" dalam kasus penghapusan aset yang dihasilkan dari tindakan kejahatan korupsi bermaksud memaksimalkan upaya untuk memulihkan / mengembalikan aset (pemulihan aset) untuk kerugian kas negara demi kepentingan keadilan bersama masyarakat, dan mekanisme tersebut tidak melanggar hak asasi manusia yang didasarkan pada penghalang antara hak atas properti yang diatur dalam "Pasal 28G Undang-Undang Dasar Negara Republik Indonesia Tahun 1945". Kata kunci: Non-Conviction Based Asset Forfeiture; Korupsi; Hukum Pidana.